The Conceptual Framework: A Supportive Accreditation Practice for Teacher Education Programs that Could be Used in the Academic Governance of Public School Districts - Kirsten Limpert; Nancy Albrecht; Stu Ervay (The Advocate, 2012)
This paper discusses how the conceptual framework - a tool used by teacher education units to improve post-secondary professional programs - can be used by public school districts instead of or in addition to a mission statement for the development of course syllabi and curriculum in this era of educational reform. It brings to a forefront the reality that public schools do not typically use the syllabus technique but instead use local curriculum guides and lesson plans. However, some districts are beginning to use comprehensive course plans similar to syllabi in higher education. Regardless of the processes being used, a framework, such as the one presented in this paper can serve as a kind of litmus test when teachers and administrators create and evaluate documents associated with curriculum and instruction as part of the school improvement process.